Studies on Physical Properties of Pelleted Onion (Allium cepa L.) Seeds - Gautam, Anand; Khurana, Rohinish; Singh Manes, Gursaheb; Dixit, Anoop Kumar (International Journal of Bio-resource and Stress Management, 2016)
Onion (Allium cepa L.) is one of the major vegetable crops grown throughout India. Pelletizing of the onion seed by providing a seed coat helps in changing the physical characteristics of the seed. Experiment was conducted for studying the physical properties of pelleted onion seed and these were compared to un-pelleted seed. The onion seed of variety Punjab Naroya (PN) was used throughout the experiment. The physical properties namely size, shape, thousand grain weight, angle of repose, bulk density and coefficient of static friction are important from engineering view point. The seeds were got pelletized in three categories i.e. the seed to coating material was in the ratio of 1:1, 1:2 and 1:3. The geometric mean diameter was measured for the three categories are 2.45, 2.82, and 3.07 mm. In comparison, the geometric mean diameter for un-pelleted seed was 2.00 mm. The average values of angle of repose for the cultivars under study as observed in the laboratory was 29.50°, 24.78°, and 23.70° respectively for Pelleted 1:1, 1:2 and 1:3 onion seeds. In comparison, the average value of angle of repose for un-pelleted seed was 31.61°. The values of porosity are decreased in gradually un-pelleted to 1:1, 1:2 and 1:3 pelleted seeds whereas the porosity for 1:3 Pelleted seed was 41.84% and is the lowest amongst the other cultivars. The porosity of un-pelleted seed was the highest (53.3%).